PERBEDAAN EFEKTIFITAS MINYAK ATSIRI BUNGA KENANGA (CANANGA ODORATA ) SEBAGAI REPELAN TERHADAP GIGITAN NYAMUK AEDES AEGYPTI DENGAN KONSENTRASI 5%, 15% DAN 25% - Ratnasari, Dewi (Coping: Community of Publishing in Nursing; Vol 2 No 3 (2014): JURNAL EDISI SEPTEMBER-DESEMBER 2014, 2014)
Dengue hemorrhagic fever (DHF) is a disease caused by a vector which is still a problem in Indonesia, therefore the efforts are made to prevent mosquito bites is very important. One of the ways to prevent Aedes aegypti bites is by using repellent as a personal protector. Repellent mechanism is contained in the smell of essential oils that seep into the pores of the skin and body heat, environment; essential oils evaporate into the air. This odor will be detected by chemical receptors found on the antennae of mosquito that it is transmitted to nerve impulses, and those impulses respond to the brain so those mosquitoes will express themselves to avoid that smell. This study aims to determine the effectiveness of essential oils as repellent ylang flowers against Aedes aegypti mosquito bites. This study is a true experiment with a completely randomized design ( completely randomized designed ). The treatment group consisted of giving flowers ylang essential oil at a concentration of 5%, 15% and 25%. Negative control group was without treatment and a positive control group was using DEET. The analysis used in this study consisted of a non-parametric test of Kruskal - Wallis and Mann Whitney test. The results of the study Kruskal-Wallis test showed that there is effective ylang flower essential oil ( Cananga odorata ) as repellent against mosquito bites Aedes aegypti with a concentration of 5%, 15% and 25% (p = 0.009, p = 0.022, p = 0.030). At the Mann Whitney test showed no difference in the effectiveness of essential oils ylang flower ( Cananga odorata ) as repellent in the treatment group and the control group. This formula can be used to determine the power of essential oils repellent DR = (K-P) / K x 100%. . Effectiveness flower ylang essential oil at a concentration of 5%, 15% and 25%, respectively for 87%, 91% and 100%. Based on research that is done, in concentration of 25% the flowers ylang essential oil can be used as repellent for Aedes aegypti mosquitoes bite
Keywords: Essential Oils, Aedes aegypti, Repellent